Cryptococcal Meningitis in A Patient With Giant Cell Arteritis - Jin LV,; Qiankun ZHANG, (Archives of Rheumatology, 2017)
Cryptococcal meningitis is a rare complication of giant cell vasculitis. Because its manifestations are very similar to those of giant cell vasculitis relapse, the diagnosis is often delayed and/or misdiagnosed. In this article, we present the case of a 65-year-old female patient who suffered from cryptococcal meningitis during high-dose steroid therapy for giant cell vasculitis.